Wide-temperature-range high-specific-energy solid-state fluorine ion battery and preparation method thereof

CN123018054APending Publication Date: 2026-10-30SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510542868.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]因此,固态氟离子电池具有高理论能量密度和高安全的潜力,但仍受限于以下问题尚需解决:(1)氟离子电池正负极材料电化学理论容量高但实际容量发挥低;(2)氟离子固态电解质氟离子电导率低、电化学稳定性差、电压窗口窄及部分氟离子固态电解质高温稳定性差;(3)氟离子固态电解质多级界面相容性差,界面阻抗高;(5)氟离子固态电池组装困难,能量密度低

Benefits of technology

本发明中,采用高性能高容量高储氟离子活性的正负极、非晶高熵氟离子固体电解质和少量增塑剂制备宽温域高比能固态氟离子电池,突破了氟离子电池长期面临的电极材料氟离子存储活性差、氟离子输运困难、电化学窗口小、电压平台低、工作温域窄等问题。所述宽温域高比能固态氟离子电池,结合了正负极材料高比容量(≥500mAh/g)、室温高氟离子电导率(≥0.5mS/cm)、宽电压窗口(≥4V)、高工作电压(≥3V)以及高比能量的优势,所述固态氟离子电池质量比能量可达200~400Wh/kg,可以在25~175℃范围内正常充放电,循环寿命超过150圈,大大增加其在先进固态氟离子电池中的可用性,极大促进新型高比能高安全固态氟离子电池发展。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018054A_ABST
    Figure CN123018054A_ABST
Patent Text Reader

Abstract

This invention relates to a wide-temperature-range, high-energy-density solid-state fluoride-ion battery and its preparation method. The solid-state fluoride-ion battery includes: a positive electrode, a negative electrode, and a solid electrolyte; the positive and / or negative electrode comprises: a positive electrode material and / or a negative electrode material, and a solid electrolyte; the positive electrode material includes a fluoride positive electrode material or an amorphous high-entropy fluoride positive electrode material; the negative electrode material is metal M and metal fluoride MF. x The composite material, wherein M is at least one of alkali metal, alkaline earth metal, rare earth metal, and Al; the solid electrolyte is an amorphous high-entropy fluoride ion solid electrolyte with the chemical formula AM. x EM y RM z F x+2y+3z AM represents alkali metal elements with different compositions, EM represents alkaline earth metal elements with different compositions, and RM represents rare earth metal elements with different compositions; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; x=a / N, y=b / N, z=c / N and the subscript corresponding to each AM, EM, and RM is 1 / N.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy, specifically relating to a wide-temperature-range high-energy-density solid-state fluoride-ion battery and its preparation method. Background Technology

[0002] The research background of solid-state fluoride-ion batteries (SSFIBs) is the search for potential alternatives to lithium-ion batteries, as well as the high energy density potential and safety advantages of fluoride-ion batteries. In discussing the necessity of researching solid-state fluoride-ion batteries (SSFIBs), we first learn that the concept of fluoride-ion batteries was proposed as early as the 1970s. Due to the small atomic weight of fluorine, rechargeable fluoride-ion batteries theoretically possess very high energy density. Traditional commercial batteries such as lithium-ion batteries face limitations in energy density improvement and resource constraints. Therefore, researchers began to explore battery systems using other elements as charge carriers, including all-solid-state fluoride-ion batteries. Fluoride-ion batteries have attracted much attention due to their high electronegativity and small ionic radius; they not only promise to provide higher energy density but also offer improved safety due to their alkali-metal-free nature.

[0003] Research progress on solid-state fluoride-ion batteries has been made both domestically and internationally. For example, Professor Ma Cheng's team at the University of Science and Technology of China designed a novel fluoride-ion solid electrolyte, CsPb. 0.9 K 0.1 F 2.9 A stable, long-cycle all-solid-state fluoride-ion battery was successfully achieved at room temperature, with almost no capacity decay during continuous charge-discharge at 25°C, demonstrating long-cycle performance and high capacity retention. Furthermore, the Shanghai Institute of Ceramics proposed a solid-state fluoride-ion battery based on a layered electrolyte structure and made related research progress. However, this system faces challenges such as the lack of highly conductive fluoride-ion electrolytes, poor electrochemical reversibility over a wide temperature range, and low energy density of solid-state fluoride-ion battery devices. In conclusion, despite these challenges, significant progress has been made in the research of solid-state fluoride-ion batteries, particularly in the development of novel solid-state electrolytes. With further research and technological advancements, solid-state fluoride-ion batteries are expected to become a strong candidate for future high-energy-density, low-cost, and safe energy storage systems.

[0004] Therefore, solid-state fluorine-ion batteries have the potential for high theoretical energy density and high safety, but are still limited by the following problems that need to be solved: (1) The electrochemical theoretical capacity of the positive and negative electrode materials of fluorine-ion batteries is high, but the actual capacity utilization is low; (2) The fluorine-ion solid electrolyte has low fluorine conductivity, poor electrochemical stability, narrow voltage window, and poor high-temperature stability of some fluorine-ion solid electrolytes; (3) The multi-level interface compatibility of fluorine-ion solid electrolytes is poor, and the interface impedance is high; (5) Fluorine-ion solid batteries are difficult to assemble and have low energy density. Summary of the Invention

[0005] Based on the problems existing in fluorine-ion solid-state batteries and the progress of previous research, this invention aims to provide a wide-temperature-range high-energy-density solid-state fluorine-ion battery and its preparation method.

[0006] On one hand, the present invention provides a wide-temperature-range high-energy-density solid-state fluoride-ion battery, comprising: a positive electrode, a negative electrode, and a solid electrolyte; wherein the composition of the positive electrode and / or negative electrode comprises: a positive electrode material and / or a negative electrode material, and a solid electrolyte; the positive electrode material comprises a fluoride positive electrode material or an amorphous high-entropy fluoride positive electrode material; the negative electrode material is metal M and metal fluoride MF. x The composite material, wherein M is at least one of alkali metal, alkaline earth metal, rare earth metal, and Al, preferably at least one of Ca, Mg, Al, Y, Sr, La, Ce, and Pb; or, the negative electrode is a metal foil, preferably a Li metal foil, Mg metal foil, La metal foil, Ce metal foil, or Y metal foil. The solid electrolyte is an amorphous high-entropy fluoride ion solid electrolyte with the chemical formula AM. x EM y RM z F x+2y+3z Wherein, AM is an alkali metal element with a different composition, EM is an alkaline earth metal element with a different composition, and RM is a rare earth metal element with a different composition; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; x=a / N, y=b / N, z=c / N and the subscript corresponding to each AM, EM, and RM is 1 / N; preferably, the amorphous high-entropy fluoride ion solid electrolyte has an amorphous amorphous structure.

[0007] In this invention, in order to achieve the fabrication of a wide-temperature-range, high-energy-density solid-state fluoride-ion battery, high-performance, high-capacity, and high-fluoride-ion-storage-activity positive and negative electrode materials and a high-fluoride-ion conductivity, wide-voltage window, and wide-temperature-range solid electrolyte are selected. By introducing a small amount of amide compounds as plasticizers, excellent interfacial compatibility is achieved at grain boundaries and multi-level interfaces between the solid electrolyte and positive and negative electrode materials. This can significantly reduce the intercrystalline resistance and interfacial impedance, thereby achieving efficient fluoride-ion storage and transport.

[0008] Preferably, the fluoride cathode material is carbon fluoride (CF). x or metal fluoride MF y Where 0.1≤x≤2, 0.1≤y≤5, and M is at least one of Cu, Fe, Ag, Bi, Mn, Cr, Ni, Co, Sn, Pb, and Mo.

[0009] Preferably, the amorphous high-entropy fluoride cathode material has the chemical formula A. x M y M' z F 2x+3y+4zWhere A is a divalent metal element with a different composition, M is a trivalent metal element with a different composition, and M' is a tetravalent metal element with a different composition; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; the subscript x corresponding to each A is 1 / 2N≤x≤(N+1) / 2N, the subscript y corresponding to each M is 1 / 2N≤y≤(N+1) / 2N, the subscript z corresponding to each M' is 1 / 2N≤z≤(N+1) / 2N, and the sum of the subscripts of A, M, and M' is 1; preferably, b and c are not simultaneously 0; more preferably, A includes Fe, Mn, Co, Ni, Cu, Pb, and Zn, M includes Al, Fe, Mn, V, Ga, Cr, Sb, Bi, and Ru, and M' includes Ti, V, Mo, Sn, Ge, Mn, and Pb.

[0010] Preferably, the wide-temperature-range high-energy-density solid-state fluorine-ion battery further includes a plasticizer of at least one of amide, carbonate, and ether compounds; preferably, the mass percentage of the plasticizer is less than 20% of the mass of the solid electrolyte.

[0011] Preferably, the conductive agent is at least one selected from carbon nanotubes, acetylene black, Ketjen black, porous carbon materials, and graphene.

[0012] Preferably, the positive and / or negative electrode further includes: a conductive agent of at least one of carbon nanotubes, acetylene black, Ketjen black, porous carbon materials and graphene; and a binder of at least one of PVDF, PTFE, SBR, CMC, PAA, PMMA, PAN, and sodium alginate; preferably, the mass ratio of the positive and / or negative electrode materials, solid electrolyte, conductive agent and binder is (60-95):(2-10):(2-20):(1-10).

[0013] On the other hand, the present invention provides a method for preparing the above-mentioned wide-temperature-range high-energy-density solid-state fluorine-ion battery, comprising: stacking a positive electrode sheet, a solid electrolyte sheet, and a negative electrode sheet in sequence, adding a plasticizer to improve the interfacial contact, and then die-casting the mixture using a pressure mold to prepare the wide-temperature-range high-energy-density solid-state fluorine-ion battery.

[0014] Preferably, the method for preparing the positive electrode and / or negative electrode includes: mixing the positive electrode material and / or negative electrode material, solid electrolyte, conductive agent and binder, and preparing it with a current collector; preferably, the current collector is at least one of aluminum foil, copper foil, stainless steel foil, titanium foil and graphite foil.

[0015] Preferably, the method for preparing the solid electrolyte sheet includes: pressing the solid electrolyte into a ceramic sheet; Alternatively, a solid electrolyte film can be prepared by combining a solid electrolyte with an organic polymer; preferably, the organic polymer is PEO, PDOL, PVDF, or PTFE; more preferably, the organic polymer accounts for 1 to 10% of the mass of the solid electrolyte. Alternatively, a solid electrolyte can be coated on both sides of the polymer film; preferably, the polymer film is PP, PE, or nonwoven fabric.

[0016] Preferably, the mass ratio of the positive electrode, the solid electrolyte sheet, and the negative electrode is (30-60%):(2-30%):(10-40%).

[0017] Preferably, the pressure of the pressure mold for die casting is controlled at 5 to 10 MPa.

[0018] Preferably, the wide-temperature-range high-energy-density solid-state fluorine-ion battery is a button cell, pouch cell, prismatic cell, or cylindrical cell.

[0019] Preferably, the wide-temperature-range high-energy-density solid-state fluoride-ion battery has a specific energy of 150–400 Wh / kg and can be charged and discharged normally within the range of 25–175°C.

[0020] Beneficial effects: This invention utilizes high-performance, high-capacity, and highly active fluoride-ion storage positive and negative electrodes, an amorphous high-entropy fluoride-ion solid electrolyte, and a small amount of plasticizer to prepare a wide-temperature-range, high-energy-density solid-state fluoride-ion battery. This overcomes the long-standing problems faced by fluoride-ion batteries, such as poor fluoride-ion storage activity in electrode materials, difficulties in fluoride-ion transport, small electrochemical window, low voltage plateau, and narrow operating temperature range. The wide-temperature-range, high-energy-density solid-state fluoride-ion battery combines the advantages of high specific capacity (≥500 mAh / g) of positive and negative electrode materials, high fluoride-ion conductivity at room temperature (≥0.5 mS / cm), wide voltage window (≥4V), high operating voltage (≥3V), and high specific energy. The solid-state fluoride-ion battery achieves a specific energy of 200–400 Wh / kg, can be normally charged and discharged within the temperature range of 25–175℃, and has a cycle life exceeding 150 cycles. This significantly increases its usability in advanced solid-state fluoride-ion batteries and greatly promotes the development of novel high-energy-density, high-safety solid-state fluoride-ion batteries. Attached Figure Description

[0021] Figure 1 The image shows the wide-temperature-range high-energy-density solid-state fluoride-ion battery device prepared in Example 1; Figure 2 This is a schematic diagram of the internal structure of the wide-temperature-range high-energy-density solid-state fluoride-ion battery device prepared in Example 1; Figure 3 The charge-discharge curve of the wide-temperature-range high-energy-density solid-state fluoride-ion battery device prepared in Example 1 at 25°C. Figure 4Charge-discharge curves of the wide-temperature-range high-energy-density solid-state fluoride-ion battery device prepared in Example 1 at 175°C; Figure 5 Cycle life data of the wide temperature range high specific energy solid fluoride-ion battery device prepared in Example 1 at room temperature (25°C); Figure 6 The wide-temperature-range high-energy-density solid-state fluoride-ion battery device prepared in Example 1 has a battery capacity at room temperature of 25°C. Figure 7 Charge-discharge curves of the solid-state fluorine-ion battery device prepared for Comparative Example 1 at room temperature (25°C); Figure 8 The charge-discharge curves of the solid-state fluorine-ion battery device prepared for Comparative Example 2 at room temperature (25°C). Detailed Implementation

[0022] To further illustrate the invention's content, features, and practical effects, the invention will be described in detail below with reference to embodiments. It should be noted that the modification methods of the invention are not limited to these specific implementation methods. Equivalent substitutions and modifications made by those skilled in the art based on their understanding of the invention, without departing from its spirit and essence, are also within the scope of protection claimed by this invention.

[0023] First, a wide-temperature-range, high-energy-density solid-state fluorine-ion battery includes: a positive electrode, a negative electrode, a solid electrolyte, and a plasticizer; the positive and / or negative electrode comprises: a positive electrode material and / or a negative electrode material, a solid electrolyte, a conductive agent, and a binder; preferably, the positive electrode material comprises a fluoride positive electrode material or an amorphous high-entropy fluoride positive electrode material; the negative electrode material is metal M and metal fluoride MF. x The composite material, wherein M is at least one of alkali metal, alkaline earth metal, rare earth metal, and Al, preferably at least one of Ca, Mg, Al, Y, Sr, La, Ce, and Pb.

[0024] In some embodiments, the fluoride cathode material is fluorinated carbon CF2. x or metal fluoride MF y Where 0.1≤x≤2, 0.1≤y≤5, and M is at least one of Cu, Fe, Ag, Bi, Mn, Cr, Ni, Co, Sn, Pb, and Mo.

[0025] In some embodiments, the amorphous high-entropy fluoride cathode material has the chemical formula A. x M y M' z F 2x+3y+4zWhere A is a divalent metal element with a different composition, M is a trivalent metal element with a different composition, and M' is a tetravalent metal element with a different composition; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; the subscript x corresponding to each A is 1 / 2N≤x≤(N+1) / 2N, the subscript y corresponding to each M is 1 / 2N≤y≤(N+1) / 2N, the subscript z corresponding to each M' is 1 / 2N≤z≤(N+1) / 2N, and the sum of the subscripts of A, M, and M' is 1; preferably, b and c are not simultaneously 0; more preferably, A includes Fe, Mn, Co, Ni, Cu, Pb, and Zn, M includes Al, Fe, Mn, V, Ga, Cr, Sb, Bi, and Ru, and M' includes Ti, V, Mo, Sn, Ge, Mn, and Pb.

[0026] In some embodiments, the negative electrode is a metal foil, preferably a Li metal foil, Mg metal foil, La metal foil, Ce metal foil, or Y metal foil.

[0027] In some embodiments, the solid electrolyte is an amorphous high-entropy fluoride ion solid electrolyte with the chemical formula AM. x EM y RM z F x+2y+3z Wherein, AM is an alkali metal element with a different composition, EM is an alkaline earth metal element with a different composition, and RM is a rare earth metal element with a different composition; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; x=a / N, y=b / N, z=c / N and the subscript corresponding to each AM, EM, and RM is 1 / N; preferably, the amorphous high-entropy fluoride ion solid electrolyte has an amorphous amorphous structure.

[0028] In some embodiments, the plasticizer is an amide, carbonate, or ether compound; preferably, the mass percentage of the plasticizer is less than 20% of the mass of the solid electrolyte.

[0029] In some embodiments, the adhesive is at least one selected from PVDF, PTFE, SBR, CMC, PAA, PMMA, PAN, and sodium alginate.

[0030] In some embodiments, the mass ratio of the positive electrode material and / or negative electrode material, solid electrolyte, conductive agent and binder is (60-95):(2-10):(2-20):(1-10).

[0031] In this invention, amorphous high-entropy fluoride cathode material and solid electrolyte are prepared by high-energy ball milling and liquid-phase oligomerization. The composite anode of the battery (comprising metal M and metal fluoride MF) x The composite material was prepared by high-energy ball milling.

[0032] In this invention, the high-entropy amorphous fluoride cathode and the high-entropy amorphous fluoride electrolyte have an interfacial synergistic effect, constructing excellent interfacial compatibility and enabling rapid migration of fluoride ions; the composite anode acts as a reaction interface enhancer to compensate for fluoride loss during the fluorination process, and alleviates volume expansion through a three-dimensional composite structure; the conductive agent significantly reduces the contact resistance of the electrode and accelerates the electron migration rate by constructing a three-dimensional conductive network between active material particles and between the active material and the current collector; and the plasticizer optimizes ion transport and interfacial stability through molecular regulation.

[0033] In this invention, the pressure needs to be controlled between 5 and 10 MPa during the assembly of the solid-state fluorine-ion battery. The pressure during battery assembly has a significant effect on performance, affecting the compactness of the solid electrolyte, ionic conductivity, and electrode structural integrity. Excessive pressure may damage the electrode materials. The operating pressure needs to maintain the electrode / electrolyte interface contact and offset material volume changes. High pressure can easily induce lattice distortion and reduce ion mobility, but appropriate pressure can suppress interface degradation.

[0034] The following is an exemplary description of the preparation method of the wide-temperature-range high-energy-density solid-state fluoride-ion battery provided by the present invention.

[0035] Preparation of positive and / or negative electrode sheets. Positive and / or negative electrode materials, solid electrolyte, conductive agent, and binder are mixed with a current collector to prepare positive and / or negative electrode sheets.

[0036] In an optional embodiment, the current collector is at least one of aluminum foil, copper foil, stainless steel foil, titanium foil, and graphite foil.

[0037] Preparation of solid electrolyte sheets. Solid electrolytes are pressed into ceramic sheets; or, solid electrolytes are composited with organic polymers to form solid electrolyte films; or, solid electrolytes are coated on both sides of a polymer film.

[0038] In an optional embodiment, the organic polymer is PEO, PDOL, PVDF, PTFE, etc., and preferably, the mass percentage of the organic polymer is 1 to 10% of the mass of the solid electrolyte.

[0039] In an optional embodiment, the polymer film is PP, PE, non-woven fabric, etc.

[0040] The positive electrode, solid electrolyte sheet, and negative electrode are stacked in sequence, and a plasticizer is added to improve the interfacial contact. Then, the mixture is die-cast using a pressure mold to prepare the wide-temperature-range high-energy-density solid fluoride-ion battery.

[0041] In an optional embodiment, the mass ratio of the positive electrode sheet, the solid electrolyte sheet, and the negative electrode sheet is (30-60%):(2-30%):(10-40%). A high mass ratio of positive and / or negative electrode materials can deteriorate interfacial contact, leading to poor cycle life; a low mass ratio can reduce battery energy density. Similarly, a high mass ratio of the solid electrolyte can also reduce battery energy density, while a low mass ratio can disrupt ion conduction pathways.

[0042] In an optional embodiment, the pressure of the pressure mold for die casting is controlled at 5 to 10 MPa.

[0043] In optional embodiments, the wide-temperature-range high-energy-density solid-state fluorine-ion battery is a button cell, pouch cell, prismatic cell, or cylindrical cell.

[0044] The high-energy-density solid-state fluoride-ion battery prepared by this invention has a specific energy of 150-400 Wh / kg and can be charged and discharged normally in the range of 25-175℃.

[0045] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0046] Example 1 Wide-temperature-range high-energy-density solid-state fluoride-ion battery devices using Sn 1 / 5 Co 1 / 5 Ni 1 / 5 Cu 1 / 5 Fe 1 / 5 F 13 / 5 Y@YF3 is used as the positive electrode material, and Mg is used as the negative electrode material. 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 72-Amino-N,N-dimethylacetamide is used as a plasticizer for the solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode material is prepared via high-energy ball milling. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive carbon nanotubes, and binder PVDF, followed by a copper foil current collector; the weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 60:10:20:10. The solid electrolyte sheet is formed by compounding the amorphous high-entropy fluoride ion solid electrolyte material with a small amount of PTFE (10% by mass) to create a solid electrolyte film. 2-Amino-N,N-dimethylacetamide is used as a plasticizer, added at 10% of the solid electrolyte mass. A fluorine-ion battery is prepared by stacking a positive electrode sheet, a solid electrolyte sheet, and a negative electrode sheet in a mass ratio of 60%:10%:30%, adding a plasticizer between the interfaces, and then die-casting the mixture at 10 MPa using a pressure mold. Figure 1 As shown in the diagram, the internal structure is as follows: Figure 2 As shown.

[0047] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃, and at a rate of 0.05C (e.g.) Figure 3-4 As shown in the figure, the fluorine-ion battery obtained in Example 1 can achieve normal charge and discharge, with a voltage plateau of approximately 2.7V. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion battery. When placed in a 25°C constant-temperature chamber, the battery can operate stably for 200 cycles (e.g., ...). Figure 5 As shown), the device capacity was tested, and the actual device capacity was 11.5 Ah (as shown). Figure 6 As shown in the figure, the energy density of the battery can be calculated to be 220Wh / kg.

[0048] Example 2 Wide-temperature-range high-energy-density solid-state fluoride-ion battery devices using Sn 1 / 5 Co 1 / 5 Ni 1 / 5 Cu 1 / 5 Fe 1 / 5 F 13 / 5 Ce@CeF3 is used as the positive electrode material, and Mg is used as the negative electrode material. 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 72-Hydroxy-N,N-dimethylacetamide is used as a plasticizer and serves as the solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode material is prepared via high-energy ball milling. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive carbon nanotubes, and binder PVDF, followed by a copper foil current collector; the weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 70:10:10:10. The solid electrolyte sheet is formed by compounding the amorphous high-entropy fluoride ion solid electrolyte material with a small amount of PTFE (10% by mass) to create a solid electrolyte film. 2-Hydroxy-N,N-dimethylacetamide is used as a plasticizer, added at 10% of the electrolyte mass. A fluorine-ion battery is prepared by stacking positive electrode sheet, solid electrolyte sheet, and negative electrode sheet in a mass ratio of 60%:10%:30%, adding plasticizer between the interfaces, and then die-casting at 10 MPa using a pressure mold.

[0049] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, revealing that it can achieve normal charge-discharge. This makes it the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. When the battery is placed in a 25℃ constant temperature chamber, it can operate stably for 150 cycles. The device capacity was tested, and the actual capacity of the device is 10.5Ah. The calculated energy density of the battery is 260Wh / kg.

[0050] Example 3 Wide-temperature-range high-energy-density solid-state fluoride-ion battery devices using Mn 0.2 / 5 Co 0.3 / 5 Ni 0.5 / 5 Cu 3 / 5 Fe 1 / 5 F 11 / 5 Ce@CeF3 is used as the positive electrode material, and Mg is used as the negative electrode material. 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 72-Hydroxy-N,N-dimethylacetamide is used as a plasticizer and serves as the solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode is prepared via a high-energy ball milling method. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion conductor, conductive agent carbon nanotubes, and binder PVDF, followed by a copper foil current collector; the weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by combining the amorphous high-entropy fluoride ion solid electrolyte material with a small amount of PTFE (10% by mass) to create a solid electrolyte film. 2-Hydroxy-N,N-dimethylacetamide is used as a plasticizer, added at 10% of the electrolyte mass. A fluorine-ion battery is prepared by stacking positive electrode sheet, solid electrolyte sheet, and negative electrode sheet in a mass ratio of 50%:20%:30%, adding plasticizer between the interfaces, and then die-casting at 10 MPa using a pressure mold.

[0051] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge and discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 12.5Ah. The energy density of the battery can be calculated to be 350Wh / kg.

[0052] Example 4 Wide-temperature-range high-energy-density solid-state fluoride-ion battery devices using Mn 0.2 / 5 Co 0.3 / 5 Ni 0.5 / 5 Cu 3 / 5 Fe 1 / 5 F 11 / 5 As a positive electrode material, Mg@MgF2 is used as a negative electrode material, and Mg... 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 72-Fluoro-N,N-dimethylacetamide is used as a plasticizer for the solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode material is prepared via high-energy ball milling. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion conductor, conductive agent carbon nanotubes, and binder PVDF, followed by a graphite foil current collector; the weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by compounding the amorphous high-entropy fluoride ion solid electrolyte material with a small amount of PTFE (10% by mass) to create a solid electrolyte film. 2-Fluoro-N,N-dimethylacetamide is used as a plasticizer, added at 10% of the electrolyte mass. A fluorine-ion battery is prepared by stacking positive electrode sheet, solid electrolyte sheet, and negative electrode sheet in a mass ratio of 60%:10%:30%, adding plasticizer between the interfaces, and then die-casting at 10 MPa using a pressure mold.

[0053] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge-discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 12.1Ah. The energy density of the battery can be calculated to be 400Wh / kg.

[0054] Example 5 Wide-temperature-range high-energy-density solid-state fluoride-ion battery devices using Mn 0.2 / 5 Co 0.3 / 5 Ni 0.5 / 5 Cu 3 / 5 Fe 1 / 5 F 11 / 5 Ca@CaF2 is used as the positive electrode material, and Mg is used as the negative electrode material. 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 72-Hydroxy-N,N-dimethylacetamide is used as a plasticizer and serves as the solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode material is prepared via high-energy ball milling. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive carbon nanotubes, and binder PVDF, followed by a copper foil current collector; the weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by directly cold-pressing the amorphous high-entropy fluoride ion solid electrolyte material into a solid electrolyte film. 2-Hydroxy-N,N-dimethylacetamide is used as a plasticizer, added at 10% of the electrolyte mass. A fluorine-ion battery is prepared by stacking positive electrode sheet, solid electrolyte sheet, and negative electrode sheet in a mass ratio of 60%:10%:30%, adding plasticizer between the interfaces, and then die-casting at 10 MPa using a pressure mold.

[0055] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge-discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 12.5Ah. The energy density of the battery can be calculated to be 300Wh / kg.

[0056] Example 6 Wide-temperature-range high-energy-density solid-state fluorine-ion battery devices utilize Fe 3 / 5 Mn 1 / 10 Co 1 / 10 Ni 1 / 10 Cu 1 / 10 F 13 / 5 Y@YF3 is used as the positive electrode material, and Mg is used as the negative electrode material. 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 7Dimethylformamide is used as a plasticizer and a solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode material is prepared via a high-energy ball milling method. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive agent carbon nanotubes, and binder PVDF, followed by a copper foil current collector. The weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by directly cold-pressing the amorphous high-entropy fluoride ion solid electrolyte material into a solid electrolyte film. Dimethylformamide is used as a plasticizer, added at 10% of the electrolyte mass. The positive electrode sheet, solid electrolyte sheet, and negative electrode sheet of the fluoride-ion battery are stacked sequentially in a mass ratio of 40%:20%:40%, with plasticizer added between the interfaces. The mixture is then die-cast using a pressure mold at 10 MPa to prepare a soft-pack fluoride-ion battery.

[0057] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge-discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 11.9Ah. The energy density of the battery can be calculated to be 250Wh / kg.

[0058] Example 7 Wide-temperature-range high-energy-density solid-state fluorine-ion battery devices utilize Fe 3 / 5 Mn 1 / 10 Co 1 / 10 Ni 1 / 10 Cu 1 / 10 F 13 / 5 As a positive electrode material, Li metal foil as a negative electrode material, Mg 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 7Dimethylformamide is used as a plasticizer and a solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode material is prepared via a high-energy ball milling method. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive agent carbon nanotubes, and binder PVDF, followed by a copper foil current collector. The weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by directly cold-pressing the amorphous high-entropy fluoride ion solid electrolyte material into a solid electrolyte film. Dimethylformamide is used as a plasticizer, added at 10% of the electrolyte mass. The positive electrode sheet, solid electrolyte sheet, and negative electrode sheet of the fluoride-ion battery are stacked sequentially in a mass ratio of 60%:30%:10%, with plasticizer added between the interfaces. The mixture is then die-cast using a pressure mold at 5 MPa to prepare a soft-pack fluoride-ion battery.

[0059] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge-discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 13Ah. The energy density of the battery can be calculated to be 350Wh / kg.

[0060] Example 8 Wide-temperature-range high-energy-density solid-state fluorine-ion battery devices utilize Fe 3 / 5 Mn 1 / 10 Co 1 / 10 Ni 1 / 10 Cu 1 / 10 F 13 / 5 As a positive electrode material, Mg metal foil is used as a negative electrode material, Mg 1 / 7 Ca 1 / 7 Sr 1 / 7 Ba 1 / 7 Y 1 / 7 La 1 / 7 Ce 1 / 7 F 17 / 7Dimethylformamide is used as a plasticizer and a solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the composite negative electrode is prepared via a high-energy ball milling method. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive carbon nanotubes, and binder PVDF, followed by a copper foil current collector. The weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by directly cold-pressing the amorphous high-entropy fluoride ion solid electrolyte material into a solid electrolyte film. Dimethylformamide is used as a plasticizer, added at 10% of the electrolyte mass. The positive electrode sheet, solid electrolyte sheet, and negative electrode sheet of the fluoride-ion battery are stacked sequentially in a mass ratio of 60%:30%:10%, with plasticizer added between the interfaces. The mixture is then die-cast using a pressure mold at 5 MPa to prepare a soft-pack fluoride-ion battery.

[0061] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge-discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 11Ah. The energy density of the battery can be calculated to be 200Wh / kg.

[0062] Example 9

[0063] Wide-temperature-range high-energy-density solid-state fluoride-ion battery devices utilize CF x As a positive electrode material, Mg metal foil as a negative electrode material, Ca 1 / 5 Sr 1 / 5 Ba 1 / 5 La 1 / 5 Ce 1 / 5 F 12 / 5Dimethylformamide is used as a plasticizer and a solid electrolyte material. The amorphous high-entropy fluoride positive electrode material and solid electrolyte are prepared via a liquid-phase oligomerization method, while the negative electrode is prepared via a high-energy ball milling method. The positive and negative electrode sheets are prepared by mixing the amorphous high-entropy fluoride positive electrode material and composite negative electrode material with a certain amount of amorphous high-entropy fluoride ion electrolyte, conductive carbon nanotubes, and binder PVDF, followed by a copper foil current collector. The weight ratio of the positive / negative electrode material, amorphous high-entropy fluoride ion electrolyte, conductive agent, and binder is 95:2:2:1. The solid electrolyte sheet is formed by directly cold-pressing the amorphous high-entropy fluoride ion solid electrolyte material into a solid electrolyte film. Dimethylformamide is used as a plasticizer, added at 10% of the electrolyte mass. The positive electrode sheet, solid electrolyte sheet, and negative electrode sheet of the fluoride-ion battery are stacked sequentially in a mass ratio of 60%:30%:10%, with plasticizer added between the interfaces. The mixture is then die-cast using a pressure mold at 5 MPa to prepare a soft-pack fluoride-ion battery.

[0064] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, and it was found that it can achieve normal charge-discharge. It is the world's first wide-temperature-range rechargeable solid-state fluorine-ion full battery. The battery can operate stably for 100 cycles when placed in a 25℃ constant temperature chamber. The device capacity was tested and the actual capacity of the device was 9Ah. The energy density of the battery can be calculated to be 150Wh / kg.

[0065] Comparative Example 1 In contrast, solid-state fluoride-ion battery devices use commercially available FeF3 as the positive electrode material, Pb metal foil as the negative electrode material, commercially available CsF as the solid electrolyte material, and do not add plasticizers.

[0066] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C, revealing that it could not achieve normal charge-discharge (e.g., Figure 7 (As shown).

[0067] Comparative Example 2 In contrast, solid-state fluoride-ion battery devices use commercially available CuF2 as the positive electrode material, Pb metal foil as the negative electrode material, commercially available CsF as the solid electrolyte material, and dimethylformamide as the plasticizer.

[0068] Constant current charge-discharge curves were tested at room temperature (25℃) and 175℃ at a rate of 0.05C. It was found that it could charge and discharge normally, but the operating voltage was extremely low, less than 0.5V, and there was no capacity after 10 cycles (e.g., ...). Figure 8 (As shown).

Claims

1. A wide-temperature-range, high-energy-density solid-state fluorine-ion battery, characterized in that, include: Positive electrode, negative electrode, and solid electrolyte; among them, The composition of the positive and / or negative electrode includes: positive electrode material and / or negative electrode material, and solid electrolyte; the positive electrode material includes fluoride positive electrode material or amorphous high-entropy fluoride positive electrode material; the negative electrode material is metal M and metal fluoride MF. x The composite material, wherein M is at least one of alkali metal, alkaline earth metal, rare earth metal, and Al, preferably at least one of Ca, Mg, Al, Y, Sr, La, Ce, and Pb; or, the negative electrode is a metal foil, preferably a Li metal foil, Mg metal foil, La metal foil, Ce metal foil, or Y metal foil. The solid electrolyte is an amorphous high-entropy fluoride ion solid electrolyte with the chemical formula AM. x EM y RM z F x+2y+3z Wherein, AM is an alkali metal element with a different composition, EM is an alkaline earth metal element with a different composition, and RM is a rare earth metal element with a different composition; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; x=a / N, y=b / N, z=c / N and the subscript corresponding to each AM, EM, and RM is 1 / N; preferably, the amorphous high-entropy fluoride ion solid electrolyte has an amorphous amorphous structure.

2. The wide-temperature-range high-energy-density solid-state fluoride-ion battery according to claim 1, characterized in that, The fluoride cathode material is fluorinated carbon (CF). x or metal fluoride MF y Where 0.1≤x≤2, 0.1≤y≤5, and M is at least one of Cu, Fe, Ag, Bi, Mn, Cr, Ni, Co, Sn, Pb, and Mo.

3. The wide-temperature-range high-energy-density solid-state fluoride-ion battery according to claim 1 or 2, characterized in that, The amorphous high-entropy fluoride cathode material has the chemical formula A. x M y M' z F 2x+3y+4z Where A is a divalent metal element with a different composition, M is a trivalent metal element with a different composition, and M' is a tetravalent metal element with a different composition; 0≤a≤5, 0≤b≤5, 0≤c≤5, a+b+c=N and N≥5; the subscript x corresponding to each A is 1 / 2N≤x≤(N+1) / 2N, the subscript y corresponding to each M is 1 / 2N≤y≤(N+1) / 2N, the subscript z corresponding to each M' is 1 / 2N≤z≤(N+1) / 2N, and the sum of the subscripts of A, M, and M' is 1; preferably, b and c are not simultaneously 0; more preferably, A includes Fe, Mn, Co, Ni, Cu, Pb, and Zn, M includes Al, Fe, Mn, V, Ga, Cr, Sb, Bi, and Ru, and M' includes Ti, V, Mo, Sn, Ge, Mn, and Pb.

4. The wide-temperature-range high-energy-density solid-state fluorine-ion battery according to any one of claims 1-3, characterized in that, The wide-temperature-range high-energy-density solid-state fluorine-ion battery further includes a plasticizer of at least one of amide, carbonate, and ether compounds; preferably, the mass percentage of the plasticizer is less than 20% of the mass of the solid electrolyte.

5. The wide-temperature-range high-energy-density solid-state fluorine-ion battery according to any one of claims 1-4, characterized in that, The positive and / or negative electrode further includes: a conductive agent of at least one of carbon nanotubes, acetylene black, Ketjen black, porous carbon materials and graphene; and a binder of at least one of PVDF, PTFE, SBR, CMC, PAA, PMMA, PAN, and sodium alginate; preferably, the mass ratio of the positive and / or negative electrode materials, solid electrolyte, conductive agent and binder is (60-95):(2-10):(2-20):(1-10).

6. A method for preparing a wide-temperature-range high-energy-density solid-state fluorine-ion battery according to any one of claims 1-5, characterized in that, include: The positive electrode, solid electrolyte sheet, and negative electrode are stacked in sequence, and a plasticizer is added to improve the interfacial contact. Then, the mixture is die-cast using a pressure mold to prepare the wide-temperature-range high-energy-density solid fluoride-ion battery.

7. The preparation method according to claim 6, characterized in that, The method for preparing the positive electrode and / or negative electrode includes: mixing positive electrode material and / or negative electrode material, solid electrolyte, conductive agent and binder, and preparing it with current collector; preferably, the current collector is at least one of aluminum foil, copper foil, stainless steel foil, titanium foil and graphite foil.

8. The preparation method according to claim 6 or 7, characterized in that, The method for preparing the solid electrolyte sheet includes: pressing the solid electrolyte into a ceramic sheet; Alternatively, a solid electrolyte film can be prepared by combining a solid electrolyte with an organic polymer; preferably, the organic polymer is PEO, PDOL, PVDF, or PTFE; more preferably, the organic polymer accounts for 1 to 10% of the mass of the solid electrolyte. Alternatively, a solid electrolyte can be coated on both sides of a polymer film; preferably, the polymer film is PP, PE, or nonwoven fabric.

9. The preparation method according to any one of claims 6-8, characterized in that, The mass ratio of the positive electrode, solid electrolyte sheet, and negative electrode is (30-60%): (2-30%): (10-40%).

10. The preparation method according to any one of claims 6-9, characterized in that, Its features are, The pressure for die casting is controlled between 5 and 10 MPa.